Структура и свойства поли(dA) · поли(dТ) и А : Т-участков ДНК. Расчеты энергии невалентных взаимодействий в системе, состоящей из регулярного полинуклеотида и двух слоев воды в его гликозидном желобе - Головинская, А.Г.; Полтев, В.И.; Чуприна, В.П. (Биополимеры и клетка, 1987)
Под влиянием взаимодействия поли(dA) · поли(dT) в волокнах и растворах с двумя слоями воды, образующей водный хребет, подобный обнаруженному в средней части двуспирального фрагмента d(CGCGAATTCGCG) в кристалле, формируется специфическая конформация полинуклеотида. Під впливом взаємодії полі(dA) · полі(dT) у волокнах і розчинах з двома шарами води, що утворює водний хребет, подібний виявленому в середній частині двоспірального фрагмента d(CGCGAATTCGCG) у кристалі, формується специфічна конформація полінуклеотиду. Interaction of poly(dA)·poly(dT) with two hydration shells forming a hydration spine similar to that found in the central part of the double-helical fragment d(CGCGAATTCGCG) in crystal to a considerable extent determines the existence of a specific polynucleotide conformation in fibers and in solutions. Atom-molecular models of these conformations with a narrow minor groove, a negative tilt and a positive propeller of the bases have been proposed. They explain a number of experimental facts concerning biologically important structural properties of DNA.